The Wiley handbook of early childhood development programs, practices, and policies - Votruba-Drzal, Elizabeth; Dearing, Eric (John Wiley & Sons, Inc., 2017)
"This unique and important bookprovides a comprehensive overview of the current theory, practices, and policies in early childhood development withinthe contexts of family, school, and community, and society at large. Moreover, it synthesizes scientifically rigorous research from an array of disciplines in an effort to identify the most effective strategies for promoting early childhood development"--Provided by publisher.